Redesign of the Statistics for Food Engineering Curriculum (Docentes 2.0 Journal, 2020)
In this project, a proposal for the study program of the statistics subject was presented, for the redesign of plans and programs of the Food engineering career in the Interdisciplinary Professional Unit of Biotechnology. A pilot group of 80 students was taken, who studied this subject in the second period of 2018, obtaining a favorable increase in their school achievement and a link with other areas that are in their curricular map. When handling interdisciplinary disciplines such as programming, microbiology, quantitative methods, packaging, packaging, design of experiments, it has been possible to apply essential contents of each of them when working with a set of data collected from a problem posed, different work talents are developed according to With information management, meta-cognitive learning, critical thinking, a problem solving management, creativity and innovative creations was developed that lead them to true conclusions, how the reinforcement of communication skills, collaboration, teamwork was achieved. , the student, acquired new strategies, being able to link several subjects at the same time in creating an experimental sketch.
Keywords: Curriculum; redesign; skills; learning